2012
DOI: 10.1016/j.joca.2012.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationship between thigh muscle mass and the development of knee osteoarthritis

Abstract: Objective Greater quadriceps strength has been found to reduce risk for symptomatic knee osteoarthritis (SxKOA) and knee joint space narrowing (JSN). However, this finding could relate to muscle mass or activation pattern. The purpose of this study was to assess whether greater thigh muscle mass protects against (1) incident radiographic (RKOA), (2) incident SxKOA or (3) worsening of knee JSN by 30-month follow-up. Design Multicenter Knee Osteoarthritis (MOST) study participants, who underwent dual energy x-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 25 publications
3
34
1
Order By: Relevance
“…Segal et al . also reported that thigh muscle mass does not appear to confer protection or worsening knee OA and insisted that knee extensor neuromuscular activation and muscle physiology were more important than muscle mass itself [48]. Instead of measuring muscle strength, we calculated and compared the physical activity derived from the IPAQ-K, although it cannot be a perfect substitute for muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Segal et al . also reported that thigh muscle mass does not appear to confer protection or worsening knee OA and insisted that knee extensor neuromuscular activation and muscle physiology were more important than muscle mass itself [48]. Instead of measuring muscle strength, we calculated and compared the physical activity derived from the IPAQ-K, although it cannot be a perfect substitute for muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Fat and muscle mass were estimated from whole‐body dual x‐ray absorptiometry (DXA) (Horizon DXA System, software version 12.0; Hologic) obtained at baseline using a published protocol . Variables of fat and lean muscle mass (referred to hereafter as muscle mass) were recorded in kilograms from DXA.…”
Section: Methodsmentioning
confidence: 99%
“…In relation to incident RKOA, the influence of poor muscle specific‐strength on the risk of RKOA development is unclear but is clinically important, since muscle specific‐strength (i.e., muscle strength per unit anatomical cross‐sectional area [ACSA]) is a potentially modifiable risk factor. Segal et al observed that poor knee extensor–specific strength did not predict incident RKOA over 30 months in the Multicenter Osteoarthritis Study (MOST). However, specific strength was calculated using entire thigh muscle mass obtained from dual X‐ray absorptiometry (DXA) and not specifically the quadriceps ACSA that is responsible for providing knee extensor strength .…”
Section: Introductionmentioning
confidence: 99%